2000
DOI: 10.1111/j.1348-0421.2000.tb01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Fimbriae Induce Adhesion of Monocytic Cell Line U937 to Endothelial Cells

Abstract: This study used the human monocytic cell line U937 to examine whether or not Porphyromonas gingivalis fimbriae could induce the adhesion of monocytes to endothelial cells. An in vitro adhesion assay was used to investigate the effects of the fimbriae on U937 cell adhesion to human umbilical vein endothelial cells (HUVEC). The fimbriae enhanced U937 cell adhesion to HUVEC in a dose-dependent manner. U937 cells adhered better to HUVEC pretreated with the fimbriae for a minimum of 2 hr than to untreated HUVEC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…We evaluated ICAM-1 expression by performing Western blot and qRT-PCR in endothelial cells infected with P. gingivalis for 24 h at an MOI of 100. Our prior work found that ICAM-1 expression and monocyte-endothelial cell adhesion were increased when endothelial cells were infected with P. gingivalis , which is consistent with the results of others [ 36 , 37 ]. In the presence of ISO-1, both the ICAM-1 protein and mRNA level induced by P. gingivalis infection were significantly decreased.…”
Section: Discussionsupporting
confidence: 92%
“…We evaluated ICAM-1 expression by performing Western blot and qRT-PCR in endothelial cells infected with P. gingivalis for 24 h at an MOI of 100. Our prior work found that ICAM-1 expression and monocyte-endothelial cell adhesion were increased when endothelial cells were infected with P. gingivalis , which is consistent with the results of others [ 36 , 37 ]. In the presence of ISO-1, both the ICAM-1 protein and mRNA level induced by P. gingivalis infection were significantly decreased.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the ability of P. gingivalis to invade primary gingival epithelial cells has been correlated with fimA expression (43). P. gingivalis fimbriae have also been reported to induce the expression of inflammatory cytokines in human gingival fibroblasts and mouse peritoneal macrophages and to induce monocyte adhesion to HUVEC (18,19,(31)(32)(33)(34)(35). A recent study has demonstrated that P. gingivalis fimbriae use molecules of the ␤-2 integrin family (CD18) on mouse macrophages as cellular receptors and that CD18 may play a functional role in signaling for the fimbria-induced expression of IL-1␤ and tumor necrosis factor from these cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the presence of P. gingivalis fimbriae has been demonstrated to increase the attachment of macrophages to endothelial cells in vitro. 22 This could result from the increased expression of adhesion receptors such as ICAM-1 from the endothelial cells in the presence of bacteria. 14 One of the consequences of increased endothelial NADH oxidase activity induced in the presence of P. gingivalis could be an increase in oxLDL levels, which also have been demonstrated to increase the adhesiveness of endothelial cells.…”
Section: Oral Bacteria-induced Foam Cell Formationmentioning
confidence: 99%